Carbon Nanotube Fabric-Based Composites for Development of Multifunctional Structures. (2019) - Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Ashrafi, Behnam; Gumienny-Matsuo, Nicholas; Park, Daesun; Li, Hao; Dénommée, Stéphane; Simard, Benoit
ABSTRACT: Carbon nanotubes (CNTs) possess impressive properties along with low density. Integration of CNTs in the form of fabrics or other preformed assemblies simplifies their handling and allows for the higher CNT content needed to better leverage their properties in multifunctional structures. Here we describe production of non-woven CNT-polyurethane fabrics made from industrial-grade CNTs via a one-step filtration method. Individual sheets were scaled to 30 cm x 30 cm size and subsequently used to fabricate thicker composites, including via lamination with itself to produce simple panels and with other materials to further tailor the nanocomposite properties and address several example applications including electrical heating, fire resistance, electromagnetic shielding, and a skin for stretchable morphing structures.